The Visual Problem of High Energy Physics, Gravitation and Cosmology (Global Journal of Science Frontier Research, 2019)
This article describes a model of Unitary Quantum Field theory where the particle is represented as a wave packet. The frequency dispersion equation is chosen so that the packet periodically appears and disappears without form changings. The envelope of the process is identified with a conventional wave function. Equation of such a field is nonlinear and relativistically invariant. With proper adjustments, they are reduced to Dirac, Schrödinger and Hamilton-Jacobi equations. A number of new experimental effects have been predicted both for high and low energies. Fine structure constant (1/137) was determined in 1988, masses of numerous elementary particles starting from electron were evaluated in 2007 with accuracy less than 1 %.2 pentaquarks, + barion, Higgs boson and particle 28 GeV were discovered 11 years later, all of them were evaluated with high accuracy before.
Keywords: unitary quantum theory; standard model; quantum electrodynamics; maxwell equations; schrdinger equation; solid state